LEMBAGA PERWAKILAN DAERAH DALAM NEGARA DEMOKRASI - Gusman, Erry (Ensiklopedia Sosial Review, 2020)
A hallmark of constitutional democracy is the idea that a democratic government is a government that has limited powers and is not justified in acting arbitrarily against its citizens. State power is divided in such a way that opportunities for abuse are reduced. By way of handing it over to several people or bodies and not centralizing the power of government in one hand or one body. Juridical formulation of these principles is famous for Rechstaat (rule of law) and Rule of Law. In the view of democratic groups that base themselves on communist ideology, they always act ambivalent towards the state. The state is seen as a coercive tool that will eventually disappear by itself, after the emergence of communist society. Karl Marx and Engels, the State is nothing but a machine used by one class to act against another class and the state is only a transitional institution used in the struggle to oppress opponents with violence. The state will eventually disappear when communism is reached because no one is oppressed.